On controllability of nonlinear impulsive integrodifferential systems - Sakthivel, Rathinasamy; Mahmudov, Nazim Idrisoglu; Nieto, Juan J.; Kim, Jeong Hoon (My University, 2008)
Many practical systems in physics, chemistry, biology and engineering have impulsive dynamical behaviors due to sudden changes at certain instants during the evolution process. These complex dynamical behaviors can be modeled by impulsive differential equations. This paper studies the exact controllability issue for nonlinear impulsive integrodifferential systems with finite delay in Hilbert spaces. Without imposing compactness condition on the semigroup operator, we establish controllability results by using a fixed point analysis approach. Finally, two examples are provided to show the usefulness of the proposed theory. The results extend and improve some recent results. Copyright © 2008 Watam Press.
Keywords: Controllability; Fixed point theorem; Mild solutions; Nonlinear impulsive systems